COGNITIVE DISORDERS IN MULTIPLE SCLEROSIS - Крупновицька-Сабадош, М. Ю.; Демчина, М. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The aim of the study was to analyze the results of neuropsychological tests and to reveal and resume cognitive disorders in patients with multiple sclerosis (MS). The Montreal Cognitive assessment (MoCA) was used for screening of cognitive impairment. 87 patients aged 38,5±5,5 with MS were under examination. The results of neuropsychological examination revealed cognitive disorders in 69% of patients. Cognitive disorders in MS are memory, attention, abstract intellection impairment, optic and constructive disorders, decrease of sensorimotor rate.